2017
DOI: 10.3389/fnmol.2017.00149
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Mechanisms of WY-14643 to Stabilize the Blood-Brain Barrier in a Model of Traumatic Brain Injury

Abstract: The blood-brain barrier (BBB) is damaged during ischemic insults such as traumatic brain injury or stroke. This contributes to vasogenic edema formation and deteriorate disease outcomes. Enormous efforts are pursued to understand underlying mechanisms of ischemic insults and develop novel therapeutic strategies. In the present study the effects of PPARα agonist WY-14643 were investigated to prevent BBB breakdown and reduce edema formation. WY-14643 inhibited barrier damage in a mouse BBB in vitro model of trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…The observed effect of WY-14643 on villin expression in our study may also be PPARα-independent. Except involvement of the PI3K pathway, intestinal cell differentiation has also been associated with activation of p38 MAPK [ 53 , 54 ], and it has been shown that WY-14643 induces phosphorylation of this protein [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed effect of WY-14643 on villin expression in our study may also be PPARα-independent. Except involvement of the PI3K pathway, intestinal cell differentiation has also been associated with activation of p38 MAPK [ 53 , 54 ], and it has been shown that WY-14643 induces phosphorylation of this protein [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain water content was measured as previously studied 27 . Animals were anesthetized with sodium pentobarbital (50 mg/kg; i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Although a large number of research projects were carried out on novel therapies for the treatment of cerebral ischemia, clinical success to date has been marginal. Several reports showed that the stabilization of the BBB during acute insults can lead to a significant reduction in brain edema and neurological damage [19,32,43]. Nevertheless, the mechanisms during cerebral ischemia are not yet sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it was shown in in vitro mouse models that co-cultivation with micro-environmental cells such as astrocytes or glioma cells significantly shortened incubation times to more in vivo relevant durations while achieving the same functional damage [29,31]. Therefore, one major objective of this study was to establish a human in vitro BBB model of cerebral ischemia that achieves a functional damage of approximately 35-60% TEER decline in less than 6 h. This TEER decline was defined in previous mouse in vitro studies as optimal for therapy testing, as too little damage makes the read-out of positive effects difficult and too much damage shows insufficient reversibility [31,32]. The other major objective was to investigate comprehensively the influences of experimental parameters on the expression of TJ proteins and ABC transporters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation